Acute Liver Failure Triggered by Haemolytic Crisis in a Glucose-6-Phosphate Dehydrogenase-Deficient Patient with Hepatitis A: A Case Report - Chathura Piyarathna; Lakitha Ratnaweera; Dulmini Thennakoon (Journal of Tropical Health, 2026)
Hepatitis A virus infection is one of the most common causes of acute viral hepatitis and usually results in a mild, self-limiting illness. (Biju Illolil Kuniyil) However, in rare cases it can progress to acute liver failure, particularly in vulnerable individuals. Glucose-6-phosphate dehydrogenase deficiency is one of the most common enzymatic disorders globally. This X-linked condition predisposes red blood cells to oxidative damage and acute hemolytic episodes triggered by infections, drugs, or foods. (Aradhana Aneja) We report a 53-year-old man who was presented with acute hepatitis and subsequently developed severe intravascular hemolysis, acute kidney injury, and acute liver failure. Fractionated bilirubin demonstrated significant indirect hyperbilirubinemia, and lactate dehydrogenase levels were markedly elevated, supporting intravascular hemolysis. A quantitative enzyme assay confirmed glucose-6-phosphate dehydrogenase deficiency. The patient developed coagulopathy and Grade II hepatic encephalopathy, fulfilling diagnostic criteria for acute liver failure. He required intravenous N-acetylcysteine, therapeutic plasma exchange, and hemodialysis. The patient recovered following multidisciplinary intensive care. This case highlights the importance of recognizing glucose-6-phosphate dehydrogenase deficiency in patients with viral hepatitis who develop disproportionate anemia and hyperbilirubinemia.